2017
DOI: 10.7554/elife.33323
|View full text |Cite
|
Sign up to set email alerts
|

Shaping of inner ear sensory organs through antagonistic interactions between Notch signalling and Lmx1a

Abstract: The mechanisms of formation of the distinct sensory organs of the inner ear and the non-sensory domains that separate them are still unclear. Here, we show that several sensory patches arise by progressive segregation from a common prosensory domain in the embryonic chicken and mouse otocyst. This process is regulated by mutually antagonistic signals: Notch signalling and Lmx1a. Notch-mediated lateral induction promotes prosensory fate. Some of the early Notch-active cells, however, are normally diverted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 87 publications
4
50
0
Order By: Relevance
“…This unexpected nding led to the analysis of heterozygous inner ears with and without complementation, and generated data which suggests that Neurog1 is dose-dependently required for nonsensory development while largely preserving neurosensory development. This may suggest that Neurog1 is involved in a binary decision to either adopt a non-sensory or neurosensory fate through an interaction with Notch signaling, a notion consistent with previous studies (15,32,33,37). Importantly, the observed non-sensory defects in the Neurog1 +/− were rescued in successfully complemented chimeric samples (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…This unexpected nding led to the analysis of heterozygous inner ears with and without complementation, and generated data which suggests that Neurog1 is dose-dependently required for nonsensory development while largely preserving neurosensory development. This may suggest that Neurog1 is involved in a binary decision to either adopt a non-sensory or neurosensory fate through an interaction with Notch signaling, a notion consistent with previous studies (15,32,33,37). Importantly, the observed non-sensory defects in the Neurog1 +/− were rescued in successfully complemented chimeric samples (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The same study suggested that Lmx1a is important in defining the non-sensory and sensory epithelium in the inner ear (Nichols et al 2008). A recent study confirms this role and shows that separation of sensory and non-sensory domains in the inner ear is regulated by mutually antagonistic signals: Notch signaling and Lmx1a (Mann et al 2017). Lmx1a regulates sensory organ segregation by antagonizing lateral induction and promoting commitment to the non-sensory fate (Mann et al 2017).…”
Section: Discussionmentioning
confidence: 75%
“…An interesting feature of the canonical prosensory markers, Sox2 and Jag1, and the canonical non-sensory marker Lmx1a, is that they are all expressed in a broad pattern throughout the otic cup as it closes [17,26,43]. However, as prosensory development begins, the expression of all three genes shifts and eventually separates over a 48 h period until Sox2 and Jag1 demarcate prosensory domains and Lmx1a is relegated to non-sensory epithelium [38,[44][45][46][47][48][49]. Fate mapping of Sox2 expression using a Sox2CreERT2 knock-in mouse has confirmed that the broad domain of Sox2 expressing cells present in in the early otic cup will form both future sensory and non-sensory tissues [50,51].…”
Section: Notch-mediated Lateral Induction Plays a Key Maintenance Rolmentioning
confidence: 99%
“…The solution to this paradox appears to come in the form of a non-sensory signal that opposes prosensory identity, with one of the key transcriptional effectors of this signal being Lmx1a. It has been demonstrated that Lmx1a is expressed in the non-sensory epithelium of the otocyst, with an initial stronger expression pattern on the medial side of the otocyst compared to the lateral side [26,43,49]. Loss of Lmx1a results in a deformed vestibular morphology suggestive of a failure to form semicircular canals and lack of a distinctly separated utricle and saccule, as well as enlarged vestibular sensory organs, often lacking separation between them [27,49].…”
Section: How Is Lateral Induction Initiated and Terminated?mentioning
confidence: 99%